The impulse society : America in the age of instant gratification - Roberts, Paul, 1961 August 2- (New York : Bloomsbury, 2014)
Drawing on the fields of economics, psychology, history and political philosophy, Roberts shows how we have become so obsessed with "maximizing returns" that we embrace virtually any means--any technology, personal tactic, or corporate strategy--that can deliver, regardless of consequences. Roberts lays out the history and geography of this new social order and charts a clear pathway toward a different and brighter future.
Part 1: I society : More better -- No confidence -- Power corrupts -- Something for nothing -- Part 2: Cracks in the mirror : Home alone -- Hard labor -- In sickness and in wealth -- Forever war -- Part 3: We society : Making space.
Includes bibliographical references (pages 269-298) and index.
Keywords: United States -- Economic conditions -- 21st century; United States -- Social conditions -- 21st century; United States -- Civilization -- 21st century; Civilization; Economic history; Social conditions; United States; Gesellschaft; Wirtschaftliches Verhalten; Soziale Situation; USA; 2000-2099; 2000 - 2099.; Economics; Business